K2RENb5O15-based lead-free relaxor ceramic material as well as preparation method and application thereof

Through component regulation and process optimization, K2ReNb5O15-based lead-free relaxation ceramic material was prepared, which solved the problems of low energy storage density and poor stability of existing lead-free dielectric ceramic materials, and achieved high energy storage density and high efficiency ceramics Applications of capacitors and high power pulse systems.

CN119462144APending Publication Date: 2025-02-18SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411420200.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Due to the low energy storage density and poor stability, existing lead-free dielectric ceramic materials are difficult to meet the requirements of device miniaturization and integration.

Method used

Through component control, K2ReNb5O15-based lead-free relaxation ceramic material is added, and MnCO3 and different rare earth elements (such as Nd, Sm, Gd, Ho) are added to optimize the chemical composition and preparation process of the ceramic.

Benefits of technology

It realizes that ceramic materials have high pressure resistance, low residual polarization strength, high saturation polarization strength, high energy storage density and high energy storage efficiency, and are suitable for ceramic capacitors and high power pulse systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462144A_ABST
    Figure CN119462144A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional ceramics, and particularly relates to a K2RENb5O15-based lead-free relaxation ceramic material as well as a preparation method and application thereof. The chemical composition of the KRN-based lead-free relaxation material disclosed by the invention is K2 (La0. 5RE0. 5) Nb5O15-2.5 mol% MnCO3, and RE is selected from one of Nd, Sm, Gd and Ho. The K2RENb5O15-based lead-free relaxation ceramic material has the characteristics of high breakdown strength, high energy storage density and the like, and is suitable for preparation and application of a ceramic capacitor and a dielectric capacitor in a high-power pulse system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional ceramics, and specifically relates to a K2RENb5O 15 Based lead-free relaxor ceramic material and its preparation method and application. Background Art

[0002] With the rapid development of the electronic information industry, energy storage devices have become a hot research target. Ceramic dielectric materials have attracted widespread attention due to their high power density and fast charge and discharge rates. At present, it has become an inevitable trend for lead-free materials to replace lead-based materials, but lead-free dielectric ceramics are difficult to meet the requirements of device miniaturization and integration due to their low energy storage density and poor stability. Based on the above, it is of great strategic significance to study energy storage ceramic capacitors. K2ReNb5O with a tungsten bronze structure with rich structural adjustability 15 The system has great research value. The system has small phase change hysteresis, moderate dielectric constant, and low overall structural density, and has the potential to achieve ultra-high energy storage density and lightweight. Summary of the invention

[0003] In view of the above technical problems, the present invention provides a K2RENb5O 15 The KRN-based lead-free relaxor ceramic material and its preparation method and application. The KRN-based lead-free relaxor ceramic prepared by the present invention through component regulation has the characteristics of high compressive strength, low residual polarization strength, high saturation polarization strength, high energy storage density and high energy storage efficiency, and is suitable for preparing ceramic capacitors and dielectric capacitors in high-power pulse systems.

[0004] In a first aspect, the present invention provides a KRN-based lead-free relaxor ceramic material. The chemical composition of the KRN-based lead-free relaxor ceramic material is: K2(La 0.5 RE 0.5 )Nb5O 15 -2.5mol% MnCO3, wherein RE is selected from one of Nd, Sm, Gd and Ho.

[0005] Preferably, the RE is Gd.

[0006] In a second aspect, the present invention provides a method for preparing a KRN-based lead-free relaxor ceramic material. The preparation method comprises the following steps: according to the chemical composition ratio of the KRN-based lead-free relaxor ceramic material, a K source, a La source, a RE source, and a Nb source are mixed, and a preliminary solid solution powder is obtained by calcining; the preliminary solid solution powder is mixed with a Mn source to obtain a final solid solution powder; the final solid solution powder is mixed with a binder and granulated, and a ceramic blank is obtained after aging, molding, and plastic removal; the ceramic blank is sintered to obtain a KRN-based lead-free relaxor ceramic material.

[0007] Preferably, the K source is K2CO3; the La source is La2O3; the Nb source is Nb2O5; and the Mn source is MnCO3.

[0008] Preferably, the RE source is selected from one of a Nd source, a Sm source, a Gd source and a Ho source; preferably, the Nd source is Nd2O3, the Sm source is Sm2O3, the Gd source is Gd2O3, and the Ho source is Ho2O3.

[0009] Preferably, the calcination temperature is 1150°C to 1300°C, and the time is less than 24 hours; preferably, the calcination temperature is 1150°C to 1200°C, and the time is 4 to 10 hours.

[0010] Preferably, the binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene and methyl cellulose; the added amount of the binder is 6wt.% to 8wt.% of the final solid solution powder.

[0011] Preferably, the aging temperature is room temperature, the time is 18 to 26 hours, preferably 22 to 26 hours; the temperature of the plastic removal is 600 to 850°C, the time is 1 to 24 hours, preferably 1 to 6 hours.

[0012] Preferably, the sintering temperature is 1150°C to 1300°C, and the time is less than 24 hours; preferably, the sintering temperature is 1200°C to 1300°C, and the time is 1 to 24 hours.

[0013] In a third aspect, the present invention provides a ceramic component, wherein the ceramic component is made of the KRN-based lead-free relaxor ceramic material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 X-ray diffraction patterns of ceramic materials prepared in Examples 1 to 4 of the present invention; Figure 2 The surface microscopic morphology of the ceramic materials prepared in Examples 1 to 4 of the present invention; wherein (a) to (d) are SEM images of Examples 1 to 4 respectively; Figure 3 It is a comparison diagram of hysteresis loops of ceramic components prepared in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0015] The present invention is further described by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0016] The KRN group (K2RENb5O 15 The chemical composition of lead-free relaxor ceramic material is K2(La 0.5 RE0.5 )Nb5O 15 -2.5mol%MnCO3. Among them, RE is selected from one of Nd, Sm, Gd, and Ho. MnCO3 accounts for K2(La 0.5 RE 0.5 )Nb5O 15 The molar ratio is 2.5%. The present invention has been verified through theoretical research and multiple experiments. The introduction of rare earth ions with different ionic radii is achieved by regulating different element combinations in KRN-based ceramic materials, so that KRN-based materials can exhibit excellent energy storage performance at room temperature. The ceramic material of the chemical composition provided by the present invention has high saturation polarization strength, low residual polarization strength, high energy storage density and high energy storage efficiency, and is expected to be applied to the field of dielectric energy storage.

[0017] The following is an exemplary description of the method for preparing the KRN-based lead-free relaxor ceramic material of the present invention.

[0018] The K source, La source, RE source and Nb source are mixed for the first time, dried for the first time and sieved for the first time according to the chemical composition ratio of the KRN-based lead-free relaxor ceramic material, calcined and cooled to room temperature with the furnace to obtain a ceramic pre-solid solution powder.

[0019] In some embodiments, the K source is K2CO3, the La source is La2O3, and the Nb source is Nb2O5. The RE source is selected from one of a Nd source, a Sm source, a Gd source, and a Ho source. Preferably, the Nd source is Nd2O3, the Sm source is Sm2O3, the Gd source is Gd2O3, and the Ho source is Ho2O3.

[0020] In some embodiments, the first mixing method is ball milling. During the ball milling process, the mass ratio of raw material: grinding ball: alcohol can be 1: (4-8): (0.8-1.3). The grinding ball can be a zirconia ball, a zirconia column, an agate ball, etc. The ball milling time can be adjusted as needed. For example, the ball milling time is 4 hours.

[0021] In some embodiments, the mesh size of the first screening may be 20 to 80 meshes.

[0022] In some embodiments, the calcination temperature is 1150°C to 1300°C, and the time is less than 24 hours; preferably, the calcination temperature is 1150°C to 1200°C, and the time is 4 to 10 hours. This allows the synthesis reaction of the KRN ceramic to fully occur. For example, the temperature is raised to the calcination temperature at a heating rate of no more than 2°C / min.

[0023] In some embodiments, after the first screening, the powder is briquette-pressed at 100-300 MPa, and then the pressed briquette is calcined and synthesized; at the same time, the briquette can be further crushed and sieved (for example, 20-80 mesh) after calcination and synthesis, thereby improving the efficiency of subsequent mixing processes such as ball milling and saving preparation time.

[0024] A Mn source is added to the ceramic pre-solid solution powder according to the chemical composition ratio of the KRN-based lead-free relaxor ceramic material, and the ceramic final solid solution powder is obtained through a second mixing, a second drying, and a second screening. The Mn source may be MnCO3.

[0025] In some embodiments, the second mixing method is ball milling. During the ball milling process, the mass ratio of raw material: grinding ball: alcohol can be 1: (4-8): (0.6-1.2). The grinding ball can be a zirconia ball, a zirconia column, an agate ball, etc. The ball milling time can be adjusted as needed. For example, the ball milling time is 12 hours.

[0026] In some embodiments, the mesh size of the second screening may be 20 to 80 meshes.

[0027] A binder is added to the ceramic final solid solution powder and granulated, and then aged, formed and discharged to obtain a KRN-based lead-free ceramic green blank.

[0028] In some embodiments, the binder may be at least one of polyvinyl alcohol, polyethylene glycol, polystyrene, and methylcellulose. The binder may be prepared into a solution with water. The concentration of the binder solution may be 6wt.% to 8wt.%. The amount of the binder added may be 6wt.% to 8wt.% of the final ceramic solid solution powder.

[0029] Aging can make the binder more evenly distributed in the powder, which helps the powder to be better formed. In some embodiments, the aging temperature can be room temperature (25° C.) and the time can be 18 to 26 hours, preferably 22 to 26 hours.

[0030] In some embodiments, the molding may be performed by dry pressing, and the molding pressure may be 100 to 300 MPa.

[0031] In some embodiments, the temperature of the plastic discharge is 600-850°C, and the time is 1-24 hours. Preferably, the temperature of the plastic discharge is 650-850°C, and the time is 1-6 hours. For example, the temperature is raised to the plastic discharge temperature at a heating rate of no more than 2°C / min.

[0032] The ceramic green body is sintered to obtain the KRN-based lead-free relaxor ceramic material.

[0033] In some embodiments, the sintering temperature is 1150-1300°C, and the time is less than 24 hours. Preferably, the sintering temperature is 1200-1300°C, and the sintering time is 1-24 hours. Such a sintering system is convenient for ceramic formation, while controlling the occurrence of component segregation. For example, the temperature is raised to the calcining temperature at a heating rate not higher than 2°C / min. The sintering atmosphere can be atmosphere (air).

[0034] In some embodiments, the KRN-based lead-free relaxor ceramic material has an energy storage density of 2 to 6 J·cm at 25° C. and 10 Hz. -3 , the energy storage efficiency is 60~80%.

[0035] The present invention also provides the use of the KRN-based lead-free relaxor ceramic material in the preparation of ceramic capacitors and dielectric capacitors in high-power pulse systems.

[0036] As an example, the KRN-based lead-free relaxor ceramic material is processed into a desired size, and after cleaning (e.g., ultrasonic cleaning), drying, silvering, and silver-sintering, a KRN-based relaxor ceramic element can be obtained. The silver-sintering can be carried out by keeping the temperature at 600 to 900° C. for 10 to 30 minutes. For example, the temperature is increased to the silver-sintering temperature at a heating rate of no more than 2° C. / min.

[0037] In summary, the KRN-based lead-free relaxor ceramic material obtained by the present invention through component regulation exhibits relaxation characteristics at room temperature, has the characteristics of high compressive strength, low residual polarization strength, high saturation polarization strength, high energy storage density and high energy storage efficiency, and is suitable for preparing ceramic capacitors for energy storage and dielectric capacitors in high-power pulse systems. Moreover, the KRN-based lead-free relaxor ceramic material of the present invention has a relatively low density, which is suitable for lightweight requirements such as ceramic capacitors and dielectric capacitors in high-power pulse systems. In addition, the preparation process of the present invention is simple and easy to industrialize.

[0038] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0039] Example 1

[0040] KRN-based lead-free relaxor ceramic material (K2(La 0.5 RE 0.5 )Nb5O 15-2.5mol%MnCO3,RE=Gd) comprises the following steps:

[0041] (1) According to the chemical composition ratio, potassium carbonate with a purity of 99%, niobium pentoxide with a purity of 99.93%, lanthanum trioxide with a purity of 99.99%, and gadolinium trioxide with a purity of 99.9% were weighed using an electronic balance (weighing accuracy to 0.001g). The weighed raw materials were placed in a nylon can, anhydrous ethanol was added to the can, and zirconia columns and zirconia balls of different sizes were used as media. The nylon can was placed on a planetary ball mill and mixed for 4 hours. The mass ratio of zirconia columns with a diameter of 15 mm and a height of 15 mm: zirconia columns with a diameter of 7.5 mm and a height of 7.5 mm: zirconia balls with a diameter of 10 mm was 4:2:3. After the ball milling is completed, the material is poured out, dried in a baking oven, and then sieved with a 40-mesh nylon sieve. The sieved mixed powder is pressed on a press into a cylindrical block with a size of 65 mm in diameter × 20 mm in height, calcined at 1180°C for 4 hours, and then crushed and passed through a 40-mesh sieve to obtain a ceramic pre-solid solution powder.

[0042] (2) The obtained ceramic pre-solid solution powder is put into the nylon tank again, and manganese carbonate powder with a powder molar ratio of 2.5% is added, and anhydrous ethanol is added to the tank not higher than 2 / 3 of the tank height, and zirconium oxide columns and zirconium oxide balls of different sizes are used as the medium, and the nylon tank is placed on a planetary ball mill for mixing for 12 hours. The mass ratio of zirconium oxide columns with a diameter of 15 mm × a height of 15 mm: zirconium oxide columns with a diameter of 7.5 mm × a height of 7.5 mm: zirconium oxide balls with a diameter of 10 mm is 4:2:3. After the ball milling is completed, the material is poured out, dried in a baking oven, and then sieved with a 40-mesh nylon sieve to obtain the finely ground ceramic final solid solution powder.

[0043] (3) Adding a polyvinyl alcohol aqueous solution with a concentration of 7wt.% to the final ceramic solid solution powder, the amount of the polyvinyl alcohol aqueous solution added is 6wt.% of the final ceramic solid solution powder, then mixing evenly and granulating, passing through a 40-mesh sieve, aging, and compression molding to obtain a small cylinder with a size of 13mm in diameter × 1mm in height, and then performing molding (molding temperature 600°C, time 2 hours). The molded body is sintered in an atmospheric atmosphere (sintering temperature 1250°C, insulation time 10 hours), and naturally cooled to room temperature to obtain the KRN-based lead-free relaxor ceramic material.

[0044] Example 2

[0045] The preparation method of the KRN-based lead-free relaxor ceramic material in this embodiment refers to that in Embodiment 1, except that the chemical formula of the KRN-based lead-free relaxor ceramic material is K2(La 0.5 RE 0.5 )Nb5O 15-2.5mol%MnCO3,RE=Nd.

[0046] Example 3

[0047] The preparation method of the KRN-based lead-free relaxor ceramic material in this embodiment refers to that in Embodiment 1, except that the chemical formula of the KRN-based lead-free relaxor ceramic material is K2(La 0.5 RE 0.5 )Nb5O 15 -2.5mol%MnCO3,RE=Sm.

[0048] Example 4

[0049] The preparation method of the KRN-based lead-free relaxor ceramic material in this embodiment refers to that in Embodiment 1, except that the chemical formula of the KRN-based lead-free relaxor ceramic material is K2(La 0.5 RE 0.5 )Nb5O 15 -2.5mol%MnCO3,RE=Ho.

[0050] Figure 1 The X-ray diffraction diagrams of the ceramic materials prepared in Examples 1 to 4 of the present invention are shown in Figure 1. It can be seen that the KRN ceramics prepared in the present invention have no impurity phase.

[0051] Figure 2 The surface microscopic morphology of the ceramic materials prepared in Examples 1 to 4 of the present invention is shown in Figure 1. It can be seen that the KRN ceramics prepared in the present invention are sintered densely. The average grain size is obtained by counting the grain size obtained by SEM scanning electron microscopy.

[0052] The energy storage and other related performance parameters of the KRN-based lead-free relaxor ceramic material of the present invention are tested by the TF Analyser 2000 equipment of aixACCTSystems. The KRN-based lead-free relaxor ceramic material is processed, cleaned, dried, and electroded to obtain a ceramic component. Specifically, the KRN-based lead-free relaxor ceramic material is processed into a desired size, and the KRN-based relaxor ceramic component is obtained by cleaning (e.g., ultrasonic cleaning), drying, and sputtering. The prepared ceramic component is subjected to a unipolar hysteresis loop test at room temperature and 10 Hz. Figure 3 The hysteresis loop comparison diagram of the ceramic components prepared in Examples 1 to 4 of the present invention. It can be seen that the energy storage density of the ceramic components prepared from the KRN-based lead-free relaxor ceramic material of the present invention increases continuously with the increase of the electric field strength.

[0053] Table 1

[0054] Table 1 shows the performance parameters of the KRN-based lead-free relaxor ceramic materials prepared in Examples 1 to 4. As can be seen from Table 1, with the incorporation of rare earth ions with a small ionic radius, the grains are refined, which is beneficial to improving the breakdown field strength; moreover, the introduction of rare earth ions with a small ionic radius can weaken the ferroelectric hysteresis of the material, reduce Pr, and help improve efficiency, thereby improving energy storage density. Compared with other embodiments, Example 1 has higher energy storage characteristics (energy storage density) and has the potential to be applied to pulse power capacitor technology. However, if the radius of the rare earth ions is too small, the material grains become larger, the breakdown field strength decreases, and the energy storage characteristics decrease.

[0055] In summary, the KRN-based lead-free relaxor ceramic material described in the present invention exhibits relaxation characteristics at room temperature. By introducing different A-site rare earth ions and regulating the rare earth ion radius, the KRN-based ceramics exhibit excellent energy storage characteristics at room temperature, which greatly improves the energy storage performance of KRN-based ceramics and is suitable for the preparation and application of ceramic capacitors and dielectric capacitors in high-power pulse systems.

[0056] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A KRN-based lead-free relaxor ceramic material, characterized in that: The chemical composition of the KRN-based lead-free relaxor ceramic material is: K2(La 0.5 RE 0.5 )Nb5O 15 -2.5mol% MnCO3, wherein RE is selected from one of Nd, Sm, Gd and Ho.

2. The KRN-based lead-free relaxor ceramic material according to claim 1, characterized in that: The RE is Gd.

3. A method for preparing a KRN-based lead-free relaxor ceramic material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: According to the chemical composition ratio of the KRN-based lead-free relaxor ceramic material, a K source, a La source, a RE source, and a Nb source are mixed and calcined to obtain an early solid solution powder; Mixing the previous solid solution powder with a Mn source to obtain a final solid solution powder; The final solid solution powder is mixed with a binder and granulated, and then aged, formed and molded to obtain a ceramic green body; The ceramic green body is sintered to obtain a KRN-based lead-free relaxor ceramic material.

4. The preparation method according to claim 3, characterized in that: The K source is K2CO3; the La source is La2O3; the Nb source is Nb2O5; and the Mn source is MnCO3.

5. The preparation method according to claim 3, characterized in that: The RE source is selected from one of a Nd source, a Sm source, a Gd source and a Ho source; preferably, the Nd source is Nd2O3, the Sm source is Sm2O3, the Gd source is Gd2O3, and the Ho source is Ho2O3.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The calcination temperature is 1150° C. to 1300° C., and the time is less than 24 hours; preferably, the calcination temperature is 1150° C. to 1200° C., and the time is 4 to 10 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: The binder is at least one of polyvinyl alcohol, polyethylene glycol, polystyrene and methyl cellulose; the amount of the binder added is 6wt.% to 8wt.% of the final solid solution powder.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The aging temperature is room temperature, and the time is 18 to 26 hours, preferably 22 to 26 hours; the temperature of the plastic removal is 600 to 850° C., and the time is 1 to 24 hours, preferably 1 to 6 hours.

9. The preparation method according to any one of claims 3 to 8, characterized in that: The sintering temperature is 1150° C. to 1300° C., and the time is less than 24 hours; preferably, the sintering temperature is 1200° C. to 1300° C., and the time is 1 to 24 hours.

10. A ceramic component, characterized in that: The ceramic component is made of the KRN-based lead-free relaxor ceramic material according to claim 1 or 2.